Regulation effect of slit-check dam against woody debris flow: Laboratory test - Xie, Xiangping; Wang, Xiaojun; Liu, Zhenzhen; Liu, Zhixuan; Zhao, Shenzhou (Frontiers in Earth Science, 2023)
Woody debris flows, i.e. debris flows carrying woody debris, are common in mountainous and forest areas in recent years. They can cause more severer hazards due to the effects of LW (woody debris larger than 1m in length and 10cm in width) comparing with debris flows without LW. However, mitigation structures for debris flows considered little about the regulation effect on LW and the influence of LW on the regulation effect of sediment. Thus, model tests were carried out to discuss the regulation effects of slit-check dam against woody debris flow. The research results demonstrated that slit-check dam can play effective regulation on woody debris flow without overflows. Once overflow occurs, sediment trapping efficiency as well as wood retention rate would dramatically decreased. The sediment trapping efficiency of the slit-check dam on debris flow without LW shared a linear relationship with the relative opening width, the height-to-width ratio of the opening and the opening density. However, it is also influenced by the wood retention rate for woody debris flow. A logarithmic relationship between sediment trapping rate and wood retention rate has been obtained. The wood retention rate is mainly determined by the ratio of LW length to the opening width, the ratio of the LW length to the channel width and the opening density of the slit-check dam. Three draining patterns of woody debris flow at the slit-check dam and three clogging types of LW at the openings of the slit-check dam were observed. Some design criteria for the structure parameters of the slit-check dam were proposed. The research results promote better understanding of the regulation effect of slit-check dam on woody debris flow and provide basis for the optimal design of slit-check dam.